Injury related adult deaths in Addis Ababa, Ethiopia: analysis of data from verbal autopsy - Aderaw Anteneh; Bilal Shikur Endris (BMC Public Health, 2020)
Abstract Background Injury related deaths are causing huge impact on families and communities throughout the world. Reports show that developing countries are highly affected by injury deaths. Ethiopia is among the countries that are highly affected by injury deaths especially road traffic accident. Previous studies in Ethiopia concerning injury deaths were mostly based on hospital records. However, in the context of Ethiopia, where majority of the deaths are happening outside health facilities, hospital-based studies cannot give the exact proportion of injury deaths. This study aimed to assess the proportion and types of injury deaths in Addis Ababa and the distribution with different socio-demographic characteristics using data from verbal autopsy. Methods We used verbal autopsy data of Addis Ababa Mortality Surveillance Program. The basic source of data for Addis Ababa Mortality Surveillance is burial surveillance from all cemeteries of Addis Ababa. We analyzed causes of injury mortality by different characteristics and tried to show the trends. Results Over the 8 years period of time injury has contributed about 7 % of the total deaths. Majority of injury related deaths were among males. Traffic accidents were the major injury related deaths for both sexes; intentional self-harm was highly observed among males compared with females. The findings of this study showed that the proportion of injury related deaths decreased with increasing age. Conclusions This study witnessed that deaths resulting from injuries are substantial health challenges in Addis Ababa. Road traffic accident is the most common cause of injury related deaths in the study area. The findings also indicated that males and the productive age groups are highly affected by injury deaths.